Contemporary Armenian literature in Turkey: The literary representation of armenian identity and history - Özdemir, Seda. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
The aim of this study is to place contemporary Armenian literature within Turkish historiography and to explore the main aspects of Armenian collective identity, memory and history. After a passive period in literary production, Armenian literature has started to revive following a passive period after the events of 1915. That revival also can be read as the reflection of the newly emerging Armenian visibility in the public sphere and the demand to demonstrate the Armenian cultural identity. In the literary works of this period, authors try to rewrite modern Armenian history, which is admitted as ruptured by the deportation from Anatolia in 1915. Therefore, they feel the need to provide the connection between the past and present to be able to display a living Armenian identity in Turkey, instead of any nostalgic memory. This historicization project also aims to rearticulate the Armenian belonging to Anatolia, which is assumed as the ancient homeland of Armenian people. By that emphasis on the history, Armenian literature functions as a tool to prove and recall the Armenian existence in the memory, history and culture of Anatolia. In that sense, the lived experiences of Armenians within modern Turkish history gain importance in the literary works whether documented or fictionalized. In conclusion, despite their different literary approaches, those literary works play a constitutive role in the construction of Armenian collective identity, memory and history.
Keywords: Armenian literature.; Armenians -- Ethnic identity.